Penyebaran Pendidikan Islam di Buol Abad XX M. - Azis, Muhammad Nur Ichsan (Rihlah: Jurnal Sejarah dan Kebudayaan, 2020)
This paper describes the process of spreading Islamic education in Buol towards the beginning of the 20th century. Islamic education is in Buol through the role of preachers and propagators of Islam who come to Buol through maritime trade routes. By using historical, heuristic, criticism, interpretation, and historiography methods, as well as a social science approach. Islamic education in Buol cannot be separated from the spreaders of Islam through the da'wah network where they also influence the development of Islamization. In Buol, Islamic education is found through the path of Sufism, and also politics by the appointment of a kadi. In addition, Islamic education developed because of the role of the aristocracy who wanted to make changes to Buol in the early 20th century. They developed education by learning from several teachers and scholars, and they also studied in several developing areas in the archipelago in the early 20th century. Tulisan ini mendeskripsikan proses penyebaran pendidikan Islam di Buol menjelang awal abad ke-20. Pendidikan Islam di buol berporses melalui peran para pendakwah dan penyebar Islam yang datang ke Buol melalui jalur niaga maritim. Dengan menggunakan metode sejarah, heuristik, kritik, interpretasi dan historiografi, serta pendekatan ilmu sosial. Pendidikan Islam di Buol tidak lepas dari peran para penyebar Islam melalui jaringan dakwah dimana mereka juga berpengaruh pada perkembangan Islamisasi. Di Buol, pendidikan Islam ditemukan melalui jalur tasawuf, dan juga politik dengan diangkatnya seorang kadi. Selain itu juga, pendidikan Islam berkembang karena peran dari kalangan bangsawan yang ingin melakukan perubahan atas Buol di awal abad ke-20. Mereka mengembangkan pendidikan dengan cara belajar ke beberapa guru dan ulama, serta mereka juga belajar ke beberapa daerah berkembang di Nusantara pada awal abad ke-20.